Randomized study comparing safety and efficacy of one shot versus serial metal telescopic dilation technique in percutaneous nephrolithotomy (Journal of Society of Surgeons of Nepal, 2017)
Introduction: Dilation of the track can be achieved by multiple incremental flexible Amplatz type, Alken metal telescoping dilators, or balloon in Percutaneous Nephrolithotomy (PCNL). Balloon dilator is the most expensive method. Both of the incremental dilation techniques are more time consuming with higher failure rates. Hence, a prospective randomized study was conducted to compare the safety and efficacy of “single shot” dilation of the nephrostomy tract by amplatz dilator with serial alken metallic telescopic dilation technique in PCNL.Methods: Of the 138 renal stone patients who underwent PCNL from January 2015 to December 2015, 100 patients were randomized into two groups. Serial tract dilation with alken metallic dilators was used in group A (n=50), and one shot dilation technique in Group B (n=50). The access tract dilation time, success rate, blood loss and complications were evaluated.Results: Both the groups were comparable in terms of mean age, location and size (largest diameter) of the stone (p>0.05). No difference was observed in the procedural success rate between groups A and B (96% v 94% respectively, p=0.64). Mean access time was similar in both groups (5.89+2.67 vs 4.98+2.0 mins, p=0.06). Complications between the groups were not significantly different. There were 6 patients with previous open stone surgery in both the groups. Previous open stone surgery did not impact procedural success rate, access time and complications in both groups.Conclusion: One-shot dilation technique is equally as effective, safe and well tolerated as metal telescopic dilation techniques even in patients with history of ipsilateral open stone surgery.